HAYAT BİLGİSİ DERSİ KAZANIMLARININ DEĞERLER EĞİTİMİ AÇISINDAN İNCELENMESİ. - YAŞAROĞLU, Cihat (Electronic Turkish Studies)
By education, it is possible to eliminate or decrease the social problems which are growing at present. Educational programs may play an active role for this purpose. It is very important for the prepared education programs not to leave on chance the gains for the solution of such social problems. While considering the fact that attitudes are developed at an early age, the requirement of the values education emerges in both gains and content of primary school courses. Examination of the gains in terms of values education programs not only offers introductory information to the teachers but also generates a data source for curriculum development centers. It should be taken in into account to provide adequate and balanced distribution of cognitive, affective and psychomotor areas in the prepared training programs. In this context, it must be known to what extent of the affective characteristics takes place in the training programs. In this study, the gains in Life Science Education Program analyzed in the term of values education. The study is limited with the second grade's Life Science curriculum and the exemined values are limited with 27 different humanistic values. Life Science in 2nd grades consists of three themes which are including a total of 94 gains. At the end of the study, it has come to a conclusion that in the theme of 'My School Excitement' 15 values of the 33 values, in the theme of "My Unique home" 9 values of 37 and in the theme of "Yesterday, Today and Tomorrow" 7 of 24 values have associated with values. Additionally, it is determined that "responsibility" is the most and "peace", "non-violent life" and "morality" are the least values that have been pointed. There is no reference to the expression of 10 values. Several recommendations based on the results of the study are presented.